Wound Repair in a Patient with Pemphigus Vulgaris: A Case Report - Risang Pawestri; Sandra Pebrianti; Hesti Platini; Yani Maryani (Indonesian Journal of Global Health Research, 2026)
Pemphigus vulgaris is a rare autoimmune disease with a prevalence of 0.1-0.5 per 100,000 people that characterized by blisters and acantholysis. Wounds in this disease tend to be extensive and wet, causing skin integrity problems. Research on local therapeutic interventions in pemphigus vulgaris is still limited. The purpose of this report is to determine the patient's response to a combination of wound care interventions with 0.9% NaCl compresses, MEBO ointment, and antibiotic tulle. This report method is a case report with primary and secondary data sources. Primary data is obtained through direct observation of the patient's objective condition, anamnesis, and physical examination. Secondary data was obtained from statements from the patient's family who had provided written consent (informed consent) and the patient's electronic medical records. The patient is a 36-year-old man with a wound scale according to the Pemphigus Disease Area Index 97/120. The patient's wound improved, where the wet wound dried and re-epithelialization occurred after 4 days of treatment with MEBO ointment and antibiotic tulle. In the dry wound, the wound appeared clean of dead skin tissue and soft hemorrhagic crusts after 0.9% NaCl compresses.